Anthropomorphism and Intentionality Improve Memory for Events. Issue 3 (3rd April 2018) - Baker, Lewis J.; Hymel, Alicia M.; Levin, Daniel T.
Abstract : Several studies have explored the determinants of anthropomorphism: the tendency to endow nonhuman agents with human features, goals, and intentions. Less is known of the cognitive benefits that may arise from anthropomorphism. Following research in narrative comprehension, we explored how the attribution of human-like features and intentional goals to nonhuman agents might benefit memory for events. Experiments 1 and 2 demonstrated that anthropomorphic descriptions and intentional goals independently contributed to improved narrative memory. A third experiment revealed that these effects were mediated by participants' attributions of agency. We conclude that anthropomorphic descriptions and intentional behavior jointly support a schematic framework for remembering events.